2014
DOI: 10.1111/jcc4.12065
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Participatory Dynamics Through Social Media Using a Multideterminant “Frame” Approach: The Case of Climategate on YouTube

Abstract: This paper offers a framework for examining the relationship between social, instrumental, and technological determinants of participation through social media (Dahlberg, 2004) using a discursive approach based in the concepts of frames and framing (Goffman, 1974;Snow & Benford, 1992

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 38 publications
1
34
1
Order By: Relevance
“…Other studies based on English web feeds (e.g., Gavin and Marshall, 2011;Koteyko, Thelwall, and Nerlich, 2010), blogs (e.g., Lockwood, 2010;Sharman, 2014) and YouTube discourses (e.g., Porter and Hellsten, 2014) also revealed significant climate change skepticism and climate science critique online. With these results in mind, one could assume that people who participate in science communication online are (often) science skeptics.…”
Section: Online Engagementmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies based on English web feeds (e.g., Gavin and Marshall, 2011;Koteyko, Thelwall, and Nerlich, 2010), blogs (e.g., Lockwood, 2010;Sharman, 2014) and YouTube discourses (e.g., Porter and Hellsten, 2014) also revealed significant climate change skepticism and climate science critique online. With these results in mind, one could assume that people who participate in science communication online are (often) science skeptics.…”
Section: Online Engagementmentioning
confidence: 95%
“…However, research on online climate change communication so far remains scarce Porter and Hellsten, 2014). It is unknown who the involved online users are.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about online climate change communication (Jaspal, Nerlich, & Koteyko, 2013;Porter & Hellsten, 2014) and the dynamics of attention and subtopics, although it is relevant: firstly, the Internet is considered to be a more important source of climate change information than family and friends (Synovate, 2010). Secondly, with regard to climate change, Internet usage increases knowledge (Special Eurobarometer 364, 2011;Zhao, 2009), the need for information (Zhao, 2009), and a high need for information also bolsters problem awareness and behavioral intentions (Taddicken, 2013).…”
Section: Climate Change Communicationmentioning
confidence: 99%
“…Research has also found that YouTube comments appear to reflect real-life communication behavior (Schultes, Dorner, & Lehner, 2013). Thus, YouTube commentary may serve as a lens for public opinion on issue importance, or even as a venue for user mobilization, learning, and opinion-formation (Jones & Schieffelin, 2009;Kirk & Schill, 2011;Porter & Hellsten, 2014).…”
Section: Youtubementioning
confidence: 99%